15% of $64

2(x-y) = 8 (where 6 is equal to x)

Simplify:

2(6-y)=8

2(6 + -1y) = 8

(6 * 2 + -1y * 2) = 8

(12 + -2y) = 8

12 + -2y = 8

Solve for variable 'y':

Now you would move all terms containing y to the left, and all other terms to the right (they already are in this case).

Add '-12' to each side of the equation:

12 + -12 + -2y = 8 + -12

Combine like terms: 12 + -12 = 0

0 + -2y = 8 + -12

-2y = 8 + -12

Combine like terms: 8 + -12 = -4

-2y = -4

Divide each side by '-2'.

y = 2 (it's already simplified)

Simplify:

2(6-y)=8

2(6 + -1y) = 8

(6 * 2 + -1y * 2) = 8

(12 + -2y) = 8

12 + -2y = 8

Solve for variable 'y':

Now you would move all terms containing y to the left, and all other terms to the right (they already are in this case).

Add '-12' to each side of the equation:

12 + -12 + -2y = 8 + -12

Combine like terms: 12 + -12 = 0

0 + -2y = 8 + -12

-2y = 8 + -12

Combine like terms: 8 + -12 = -4

-2y = -4

Divide each side by '-2'.

y = 2 (it's already simplified)